Fields in the southern coastal region of the Pampa Biome (Research, Society and Development, 2020)
In order to detect patterns of rural vegetation in the coastal region of the Pampa Biome, a floristic survey of a natural pasture located on the Southern Coastal Plain in Rio Grande do Sul, in the buffer zone of the Ecological Reserve of Taim (32 ° 32'03.27 S” and 52 ° 31'43.98 ”O), was conducted. The evaluations were carried out by in frames 0,25m² to estimate the botanical composition and the Daubenmeire scale was used to assess plants coverage. Aiming to detect possible patterns of vegetation variation in a Entisols Quartzipsamments, sandy texture, flat relief, lake and marine sediment substrate, the sample units were distributed in order to characterize three visually contrasting conditions: I - higher relief, with greater drainage and high proportion of bare soil (> 30%); II - intermediate relief, medium drainage and medium proportion of uncovered soil (10 to 20%); III.- lower relief, higher humidity and lower proportion of uncovered soil (